Sensitivity of CO2 and CH4 Annual Cycles to Different Meteorological Variables at a Rural Site in Northern Spain - Isidro A. Pérez; M. Luisa Sánchez; M. Ángeles García; Nuria Pardo (Advances in Meteorology)
The focus of the current paper is to explore the influence of meteorological variables on atmospheric CO2 and CH4 mean annual cycles at a rural site. Four variables were investigated: boundary layer height, recirculation factor, trajectory direction, and wind speed modelled at the altitude of the site. Boundary layer height and wind speed were provided by the METeorological data EXplorer (METEX) model. Recirculation factor and trajectory direction were obtained from calculations based on this trajectory model, and a nonparametric procedure was used to obtain a smooth evolution. The main results are higher concentrations obtained during the night, attributed to lower dispersion in this period. The smoothed values of the boundary layer height reached nearly 1200 m AGL during the day in August, and its low values caused high concentrations in spring. During the night, the recirculation factor and wind speed showed a sharp contrast between summer and winter. The average recirculation factor was low, 0.10, and average wind speed was 5.1 m·s−1. Trajectories were directionally distributed in four quadrants. Different tests were performed by selecting values of meteorological variables above or below certain thresholds. The influence of these variables reached values around 6.3 and 0.023 ppm for CO2 and CH4 average concentrations, respectively, during the day when the boundary layer was below 400 m. The main conclusion of this study is that the influence of meteorological variables should not be ignored. In particular, extremely low boundary layer heights may have noticeable effects on both gases.